A comparative study of the organizational structures of three high schools in Roxas City in terms of delegation of functions. - Langurayan, Rolando Conlu (Animo Repository, 1978)
This study aims: 1) to develop an organizational model of a high school 2) compare the organization of three high schools with the model and 3) develop for one school, a proposed program to upgrade its organizational structure. The data used in this study were supplied by three secondary principals of the three high schools in Roxas City. It covers one public high school, one catholic high school and one archdiocesan high school. The study partakes of a descriptive and exploratory nature, relevant only to conditions obtained in the specific area that has been studied.